Relationship Between Body Mass Index, Lipid Profile and Dental Caries - Fatemeh Ahmadi-Motamayel; Hamidreza Abdolsamadi; Mohammad Taghi Goodarzi; Zohreh Jamshidi; Ali Mahdavinezhad (Islamic Dental Association of Iran, 2018)
Background and Aim: Dental caries is the most common infectious, non-communicable, chronic disease worldwide. Obesity and overweight are major public health problems. Both dental caries and obesity have multi-factorial etiology. The aim of the present study was to determine the possible correlation between the body mass index (BMI), lipid profile and dental caries in two groups of high-school students with active caries (AC) and no caries (CF) in Hamadan, Iran. Materials and Methods: In this case-control study, 118 high-school students between 15-19 years were divided into two groups of AC and CF. All clinical examinations were carried out by a single examiner. Blood samples were obtained from the antecubital vein. Lipid profile was assessed by the enzymatic method using an auto-analyzer. Data were analyzed using Stata.11 software. Statistical comparisons were made using Stu-dent's t-test and chi-square test. Results: BMI was significantly lower in AC group than CF group (P=0.008). Males had higher BMI than females (P=0.056). CF group had significantly lower level of triglycer-ides (P=0.01), cholesterol (P=0.02) and low-density lipoprotein (LDL) (P=0.02) than AC group. Conclusion: Our results showed that dental caries adversely affects the systemic growth pattern, and students with dental caries had lower BMI than others. Altered lipid profile had a higher frequency in AC group. Dental caries and obesity are both multi-factorial diseases; hence, well-designed epidemiologic studies on the same age group need to be performed in the future taking into account the socioeconomic and cultural factors.